O imaginário da educação no romance Estrada da liberdade, de Alina Paim - Santos, Fabiana dos (2011)
This paper has two integrated objectives: the first one concerns the presentation and dissemination of the academic work of Alina Paim, particularly her first novel The Freedom Road (1944), and the second one refers to analysis of the imagery of female education through the Bildungsroman theory in the work of the writer in question. The work is addressed in two dimensions: the formation of the image of woman / teacher and its social context, which brings us to the theme of struggle of gender and proletarian class exposed by Paim in her work. This analysis, that goes from the history of female education to the construction of the ideals of the teacher in society, seeks to draw a perspective of how women have achieved their independence in social and personal contexts, moving from private to public areas, without losing the essence. A second dimension of the study is the analysis of traces of female education and transformation (the Bildung), through education, within the literary work. In the novel The Freedom Road, the trajectory of Marina is a fine example of how education and female instruction, even with the strong social stereotypes present at the time, change the position of women to others and to herself. In order to accomplish these goals, The material used was the theoretical support from the studies of history and women's education by Mary Del Priore, Guaraci Lopes Louro, Jane Adams, Elodia Xavier, among others, regarding the history of the process of educational and professional formation of women in Brazil; Cristina Ferreira Pinto, Wilma Patricia Maas, Eduardo Assis Duarte, among others, regarding the Bildungsroman theory, or novel of formation and learning, which fits our work perfectly. This research aims to lead to a reflection that focuses on women's position in society which was already discussed by Paim in the 40's, being inserted into the literary tradition, and giving proof to the changing role of education and the novel female formation.